Buprenorphine: revisiting the efficacy of transdermal delivery system. (April 2015) - Kitzmiller, Joseph P; Barnett, Christopher J; Steiner, Nathan S; Stoicea, Nicoleta; Kamar, Nawal; Luzum, Jasmine A; Mikulik, Eduard; Bergese, Sergio D
Introduction: Buprenorphine is a lipid-soluble pharmaceutic used in the management of chronic pain. It is a partial agonist at μ-opioid receptors, an antagonist at κ-opioid receptors, an agonist at δ-opioid receptors and a partial agonist at ORL-1 (nociceptin) receptors.Methods : An extensive literature search, including Google Scholar and Pubmed database, was conducted. Terms including and associated to 'efficacy of transdermal buprenorphine' were utilized to procure contemporary research articles in order to evaluate and compare the transdermal buprenorphine patch to commonly used traditional pain management medications.Results: Transdermal buprenorphine has demonstrated better efficacy than conventional pain management pharmacotherapies. Side effects were similar to those associated with other opioids and included headache, dizziness, somnolence, constipation, dry mouth, nausea, vomiting, pruritus and erythema. Similar to transdermal delivery systems used with other medication, transdermal buprenorphine was associated with application-site pruritus and application-site reactions.Conclusion: Transdermal buprenorphine has significant potential for managing chronic pain. In addition to increased convenience and efficacy, advantages of transdermal buprenorphine include decreased tolerance and decreased withdrawal.